A study on the impact of R&D intensity on business performance: Evidence from South Korea - Hun Park; Jun-Hwan Park; Hyuk Hahn (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The role of R&D (research and development) intensity on the effect of knowledge services on the business performance of firms has been discussed by using PLS-SEM and PLS-MGA methods. Research groups were divided into two groups, innovative and non-innovative. Respondents were classified into innovative firms if their R&D intensity was over 3% and vice versa. PLS-SEM and PLSMGA results were compared for two groups and valuable insights were extracted. For innovative firms, knowledge services seemed to be verified and processed by the decision makers and utilized to achieve their business performance. On the other hand, a large number of non-innovative firms seemed to have a stronger tendency to utilize knowledge services directly for their business without sufficient verification by the decision makers.
Keywords: 650; knowledge service; business performance; R&D intensity; decision making; PLS-SEM; PLS-MGA; open innovation